Writing Argumentative Essays: Jambi EFL Students' Challenges and Strategies - Ananda, Chairani Resti; Mardiah, Radiatan; Fajaryani, Nunung (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
Argumentative writing is a genre of writing that is considered difficult by EFL students at the university level. This study aimed to investigate problems faced by EFL students in writing an argumentative essay and to explain their strategies to overcome the problems. The participants of this study were ten fifth-semester students of the 2023-2024 academic year at the English Education Study Program of a public university in Jambi, Indonesia. A qualitative research design with a case study approach was applied. A semi-structured interview was conducted to collect the main data, and document analysis was carried out to support it. Furthermore, the data were analyzed using thematic analysis. The findings revealed that problems faced by EFL students in writing an argumentative essay include: 1) argument development problems, such as generating and developing arguments, organizing or structuring arguments, creating an argumentative thesis statement, and a lack of counterclaim and refutation knowledge, and 2) research or source integration problems, such as finding supporting evidence and a lack of writing citation knowledge. Meanwhile, strategies used by EFL students to overcome the problems include 1) information acquisition strategies by reading a lot of sources, watching videos, and looking at essay examples, 2) technology utilization strategies by using AI applications, and 3) review and improvement strategies by re-checking and revision and asking for feedback.